2008
DOI: 10.1016/j.jadohealth.2007.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Trauma Exposure and Smoking in a Population-Based Sample of Young Adults

Abstract: Purpose-To evaluate the relationship between smoking and trauma exposure in a populationbased, longitudinal sample. Contrary to current smoking trends in the general population, recent findings indicate continued high smoking rates in trauma-exposed samples.Methods-A nationally representative sample of 15,197 adolescents was followed from 1995 (mean age=15.6) to 2002 (mean age=22) as part of 3 waves of The National Longitudinal Study of Adolescent Health (Add Health). We examined the relation between self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 34 publications
3
57
1
Order By: Relevance
“…For instance, gender-stratified models revealed that past-year sexual assault was associated with smoking status among heterosexual and bisexual women but not lesbians, even though lesbians and heterosexual women had similar prevalence of sexual assault. Given research demonstrating that female survivors of sexual assault have increased risk of smoking (Acierno et al, 2000;Cloutier, Martin, & Poole, 2002;Roberts et al, 2008), this lack of association for lesbians may be an artifact of relatively smaller sample size, as there were over four times as many heterosexual women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, gender-stratified models revealed that past-year sexual assault was associated with smoking status among heterosexual and bisexual women but not lesbians, even though lesbians and heterosexual women had similar prevalence of sexual assault. Given research demonstrating that female survivors of sexual assault have increased risk of smoking (Acierno et al, 2000;Cloutier, Martin, & Poole, 2002;Roberts et al, 2008), this lack of association for lesbians may be an artifact of relatively smaller sample size, as there were over four times as many heterosexual women.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, certain types of victimization, such as intimate partner violence, sexual assault, and traumatic events, can be independent risk factors for continued smoking (Amstadter et al, 2009;Roberts, Fuemmeler, McClernon, & Beckham, 2008;Stueve & O'Donnell, 2007). Prior work with adolescent and young adult racial minorities demonstrates associations between racial-and ethnic-based discrimination and smoking (Guthrie, Young, Williams, Boyd, & Kintner, 2002;Landrine & Klonoff, 2000;Wiehe, Aalsma, Liu, & Fortenberry, 2010).…”
Section: Associations Of Discrimination and Violence With Smoking Amomentioning
confidence: 99%
“…Demographic variables included the following: age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and ‡50 years); race (white vs. other); education (less than HS, HS diploma, General Educational Development (GED), and >high school diploma); marital status (married, divorced or separated, widowed, never been married, and living with a partner); annual household income; number and age of people living at residence of participant; and health insurance (private, government assisted, or none). In addition, the following measures were collected and/or variables derived.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16] For instance, regional differences in smoking prevalence persist for women Ohio Appalachian residents, and smoking is an established risk factor linked to elevated cervical cancer incidence and mortality in the region. 1,3 In Ohio Appalachia, in 2012, 32.1% of women aged 19 and older smoked every day or some days-compared with 22.7% in metropolitan regions, 24.4% in rural non-Appalachian regions, and 23.3% in suburban regions of the state. 17 Among Ohio Appalachian women, risk factors for smoking include low socioeconomic position in adulthood, depressive symptoms, first pregnancy before age 20, and younger age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation